2012
DOI: 10.1117/12.2001103
|View full text |Cite
|
Sign up to set email alerts
|

Simulation results of optoelectronic photocurrent reconfigurable (OPR) universal logic devices (ULD) as the universal circuitry basis for advanced parallel high-performance processing

Abstract: The conception of construction of the family of the offered optoelectronic photocurrent reconfigurable (OPR) universal or multifunctional logic devices (ULD) consists in the use of a current mirrors realized on 1.5µm, 0.35µm, 65nm technology CMOS transistors. Presence of 44 transistors, 1÷5 photo-detectors makes the offered circuits quite compact and allows their integration in 1D and 2D arrays. The simulation results of the OPR ULD on the 1.5µm, 0.35µm, 65nm technology CMOS transistors showed that the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…[ 3–5 ] Optoelectronic logic devices are important elements in optoelectronic circuits, which perform logical processing with optical signals and electrical signals. [ 6–10 ] Compared to traditional electrical logic devices, optoelectronic logic devices achieve both fast operating speed and large bandwidth, [ 11 ] and the non‐interference between the optical input and the electrical input ensures parallel information detection and processing. [ 12–14 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3–5 ] Optoelectronic logic devices are important elements in optoelectronic circuits, which perform logical processing with optical signals and electrical signals. [ 6–10 ] Compared to traditional electrical logic devices, optoelectronic logic devices achieve both fast operating speed and large bandwidth, [ 11 ] and the non‐interference between the optical input and the electrical input ensures parallel information detection and processing. [ 12–14 ]…”
Section: Introductionmentioning
confidence: 99%
“…2. The significant difference of the proposed cell R MCL D from previously considered in papers 25,26 is that for all CL functions formed with TPC signals there is start-stop binding for the start of conversion. For some functions in the same papers 25, 26 such binding was not.…”
Section: Simulation Of the Base Cell R MCL Dmentioning
confidence: 92%
“…This shows that in principle it is possible to increase the frame processing rate to 10 MHz, but at the expense of accuracy and complexity of matching photodetectors with current mirrors. The simulation results of similar functionality of universal reconfigurable logic devices with dynamic photodiode controls were shown in paper 26 . It has been shown that for high-speed and simple implementation it is required not the complication of the base cell to improve conversion accuracy, and the analog processing, but the use of electrical signals to select required CL function.…”
Section: Simulation Of the Base Cell R MCL Dmentioning
confidence: 98%